¿Todavía tienes preguntas de matemáticas?

Pregunte a nuestros tutores expertos
Algebra
Pregunta

2) Given equation \( y = - 3 ( x + 5 ) ^ { 2 } - 4...

2) Given equation \( y = - 3 ( x + 5 ) ^ { 2 } - 4 \) has been transformed from \( y = x ^ { 2 } \) . Answer the following questions for \( y = - 3 ( x + 5 ) ^ { 2 } - 4 \) 

\( 1 \) point unless stated otherwise) 

a) Write in general form: \( a x ^ { 2 } + b x + c \) 

b) Direction of opening: 

c) Vertex: 

d) Equation for axis if symmetry: 

e) State it will be max or min value and state the value: 

f) Domain: 

g) Range: 

h) State all of the transformations that were applied to the function \( y = x ^ { 2 } \) to change it into the \( y = - 3 ( x + 5 ) ^ { 2 } - 4 \) . 

Answer

\(a)y= -3(x+ 5)^2- 4= -3(x^2+ 10x+ 25)- 4= -3x^2- 30x- 79\\b)downward\\c)(- 5,- 4)\\d)x= -5\\e)max: -4\\f)R\\g)(- \infty ,- 4]\\\)

h) The x value remains the same, and the y becomes -3 times the original value; then it translates 5 units to the left and 4 units down.

Solución
View full explanation on CameraMath App.